2012
DOI: 10.2165/11599040-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Antihypertensive Drugs in Arterial ‘De-Stiffening’ and Central Pulsatile Hemodynamics

Abstract: Arterial stiffness is an independent predictor of cardiovascular (CV) morbidity and mortality in patients with hypertension, as well as a potential therapeutic target. There is increasing awareness that the pulsatile hemodynamics (central blood pressure [CBP], pulse pressure [PP], wave reflections [augmentation index or AIx] and pulse wave velocity [PWV]) may provide better insight into the pathophysiology of CV disorders and target organ damage related to hypertension. Different antihypertensive drugs produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
2
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 126 publications
1
34
2
14
Order By: Relevance
“…Arterial stiffness is an independent predictor of CV morbidity and mortality in patients with hypertension, as well as a potential therapeutic target 69 . A large number of studies reports the association between hypertension and arterial stiffness (SBP, PP, AIx and PWV) (ref.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial stiffness is an independent predictor of CV morbidity and mortality in patients with hypertension, as well as a potential therapeutic target 69 . A large number of studies reports the association between hypertension and arterial stiffness (SBP, PP, AIx and PWV) (ref.…”
Section: Hypertensionmentioning
confidence: 99%
“…Their common features are likely arterial dilating capacity and the ability to reduce pressure wave reflections, such as expressed by the augmentation index 69 . These topics are extensively discussed in other reviews and exceed the focus of this article.…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…There are recent studies about the relationship between the BP and the autonomic nervous system. 2,3 In the present study, 1 the authors concluded that the patients with PD who received treatment previously had significantly higher nighttime diastolic BP than those who did not receive treatment. However, the drugs used by the patients with PD were not reported by Alici et al 1 Therefore, it would be useful to specify which drugs were used because some drugs like antidepressants and b-blockers may affect the circadian variation in BP measurements and autonomic system.…”
mentioning
confidence: 46%
“…Therefore, the probable beneficial effect of several antihypertensive and other agents, known to affect arterial function, on markers of arterial stiffness has been investigated [32]. Antihypertensive drugs, particularly renin-angiotensin-aldosterone system inhibitors, were shown to exert favourable effects on arterial stiffness and central blood pressure indices [33]. A study in end-stage CKD patients demonstrated that the absence of pulse wave velocity decrease in response to blood pressure decrease was an independent predictor of all-cause and cardiovascular mortality.…”
Section: "Anti-calcifying" and "De-stiffening" Treatment Strategies Imentioning
confidence: 99%